Study of prostatic pathology and its correlation with prostate specific antigen level - S Hirachand; UMS Dangol; S Pradhanang; S Acharya (Association of Clinical Pathologists of Nepal, 2017)
Background: Diseases primarily inflicting prostate gland are inflammation, benign prostatic hyperplasia and cancer. Prostate specific antigen is a protein produced by the cells of prostate gland. It has been widely used in the diagnosis and management of patients with prostatic cancer. The aim this study was to determine the correlation between serum prostate specific antigen level and histological findings in biopsy specimens of men with prostatic disease. Materials and methods: This study was carried out at Kathmandu Medical College and Teaching Hospital, department of Pathology over a period of 2 years. One hundred and twenty eight cases with prostatic lesions were included in this study. Prostate specific antigen values of these cases were recorded before the surgical process. Histology of the tissue samples collected after transurethral resection of prostate was studied and relationship with prostate specific antigen level were analyzed. Results: Benign prostatic hyperplasia was the most common histological lesion encountered (n=95; 74.22%). Prostatic adenocarcinomas were seen a decade older than those with benign lesions. Maximum number of the benign cases had the Prostate specific antigen range of 0-7ng/ml. Most of the prostatic intraepithelial neoplasia lesions were seen within the PSA range of 0-7ng/ml and adenocarcinoma in the range of >20ng/ml. Conclusion: Prostate specific antigen is specific for the prostate but not for prostate cancer. Both benign and malignant lesions in prostate can cause increase in serum prostate specific antigen levels, but the chances of malignancy it rising level.